We're asked to find the derivative
d/(dx) [(cos^3x)(sin^2x)]ddx[(cos3x)(sin2x)]
The first step we could do is use the product rule, which is
d/(dx) [uv] = v(du)/(dx) + u(dv)/(dx)ddx[uv]=vdudx+udvdx
where in this case
-
u = cos^3xu=cos3x
-
v = sin^2xv=sin2x:
= cos^3x(d/(dx)[sin^2x]) + sin^2x(d/(dx)[cos^3x))=cos3x(ddx[sin2x])+sin2x(ddx[cos3x))
We can differentiate the sin^2xsin2x term via the chain rule, which would look like
d/(dx)[sin^2x] = (du^2)/(du)(du)/(dx)ddx[sin2x]=du2dududx
where
d/(du) [u^2] = 2uddu[u2]=2u (power rule):
= cos^3x(2d/(dx)[sinx]sinx) + sin^2x(d/(dx)[cos^3x))=cos3x(2ddx[sinx]sinx)+sin2x(ddx[cos3x))
The derivative of sinxsinx is cosxcosx:
= cos^3x(2cosxsinx) + sin^2x(d/(dx)[cos^3x))=cos3x(2cosxsinx)+sin2x(ddx[cos3x))
Simplifying:
= 2cos^4xsinx + d/(dx)[cos^3x]sin^2x=2cos4xsinx+ddx[cos3x]sin2x
We now use the chain rule again for differentiating the cos^3xcos3x term:
d/(dx)[cos^3x] = (du^3)/(du)(du)/(dx)ddx[cos3x]=du3dududx
where
= 2cos^4xsinx + 3cos^2xd/(dx)[cosx]sin^2x=2cos4xsinx+3cos2xddx[cosx]sin2x
The derivative of cosxcosx is -sinx−sinx:
= 2cos^4xsinx - 3cos^2xsinxsin^2x=2cos4xsinx−3cos2xsinxsin2x
Simpligying gives
= color(blue)(2cos^4xsinx - 3cos^2xsin^3x=2cos4xsinx−3cos2xsin3x